Impact of Leukoaraiosis Burden on Hemispheric Lateralization of the National Institutes of Health Stroke Scale Deficit in Acute Ischemic Stroke. Issue 1 (January 2016) - Helenius, Johanna; Goddeau, Richard P.; Moonis, Majaz; Henninger, Nils
Abstract : Background and Purpose—: The National Institutes of Health Stroke Scale (NIHSS) awards higher deficit scores for infarcts in the dominant hemisphere when compared with otherwise similar infarcts in the nondominant hemisphere. This has been shown to adversely affect stroke recognition, therapeutic decisions, and outcome. However, factors modifying the association between infarct side and deficit severity are incompletely understood. Thus, we sought to determine whether age and age-related leukoaraiosis alter the relation between NIHSS deficit score and the side and volume of infarction. Methods—: We studied 238 patients with supratentorial, nonlacunar ischemic infarcts prospectively included in our stroke registry between January 2013 and January 2014. NIHSS deficit severity was assessed at the time of presentation. Infarct volumes were assessed by manual planimetry on diffusion-weighted imaging. Leukoaraiosis burden was graded on fluid-attenuated inversion recovery images according to the Fazekas scale and dichotomized to none-to-mild (0–2) versus severe (3–6). Multivariable linear regression with backward elimination was used to identify independent predictors of the admission NIHSS. Results—: Left-hemispheric infarction ( P <0.001), severe leukoaraiosis ( P =0.001), their interaction term ( P =0.005), infarct volume ( P <0.001), and sex ( P =0.013) were independently associated with the NIHSS deficit. Analysis of the individual NIHSS components showed that severe leukoaraiosis was associated with an increase of the lateralizing components of the NIHSS in patients with right-hemispheric infarction ( P <0.05). Conclusions—: Severe leukoaraiosis substantially attenuates the classic hemispheric lateralization of the NIHSS deficit by relating to greater NIHSS scores of components that are typically assigned to left hemisphere function.